PEMBERDAYAAN KELOMPOK TERNAK SUNGAI NIPAH SAIYO MELALUI PEMBUATAN FORMULA RANSUM AYAM KAMPUNG MENGANDUNG TEPUNG RUMPUT LAUT TURBINARIA MURAYANA FERMENTASI - Sepri Reski; Ridho Kurniawan Rusli; Zurmiati Zurmiati; Fea Firdani; Rifqy Rahman (Jurnal Hilirisasi IPTEKS, 2023)
This activity aims to empower the Sungai Nipah Saiyo Livestock Group in Pesisir Selatan Regency by innovating village chicken feed using fermented Turbinaria murayana seaweed flour as a substitute for fine bran. The goal is also to reduce the use of ground corn and concentrate on village chicken feed. The activity method involves training/demonstrating and assisting livestock groups in developing and utilizing a new feed formulation based on fermented Turbinaria murayana seaweed flour. The results show that implementing the feed formula containing fermented Turbinaria murayana seaweed flour can increase village chicken productivity and significantly reduce feed costs, positively impacting the economic empowerment of the livestock group. Additionally, this initiative promotes environmental sustainability by utilizing the abundant local marine resource, Turbinaria murayana brown seaweed, along the coastal area of the Nipah River in Pesisir Selatan Regency. The conclusion drawn from this activity is farmers' increased knowledge and skills in formulating village chicken feed with Turbinaria murayana seaweed flour, evident in the enthusiastic participation of group members in training and the application of the provided formula in village chicken maintenance. This initiative contributes positively to the community's welfare in the Nipah River area of Pesisir Selatan Regency.